PENGARUH TEMPERATUR DAN KETEBALAN BENDA COR TERHADAP SIFAT MEKANIK PADA PROSES PENGECORAN ALUMUNIUM - Taufikurrahman, Taufikurrahman; Sundari, Ella (AUSTENIT, 2015)
Casting process in small industries were using plain technology and recycled non-ferrous materials (such as aluminum, brass and copper). Casting was done by using sand mold casting and the casting systems were used kerosene furnace. The main constraint of such technology is that it is impossible to do diversification of products which have high sales value like souvenir products. These products are generally in form of sheets in various types of souvenirs which hardly be produced with existing casting technology. Material development will be determined the structure and properties of the optimum materials. The composition of aluminum alloy are 84.4% Al, 0.357% Ni, 2.74% Fe, 2.42% Cu, 0.179% Mn, 1.99% Zn, Sn 0.066%, 0.0704% Pb,Â  0061% Ti, and 0.066 Bi, where the influence of rising temperature causes the percentage of Mn, Zn, Mn, Mg Pb, Sn and Ti to decreased as a result of the evaporation process. Surface hardness decreased due to the increase in temperature, while the surface thickness has no effect.Â  The highest surface hardness found in 3 mm of cast thickness with temperature 650oC and 86.58 HBN. The endurance to impact loads is 3,36 Nm in 10 mm of thickness and temperature 750oC.